Value co-creation through multiple shopping channels: The interconnections with social exclusion and well-being - Dennis, Charles; Bourlakis, Michael; Alamanos, Eleftherios; Papagiannidis, Savvas; Brakus, J. Joško (Taylor & Francis, 2017)
This study examines consumers’ value co-creation via several shopping channels including a traditional out-of-home shopping channel and “smart” channels where consumers use a computer, a mobile phone, or social media. It focuses on the effect that value co-creation has on consumers’ shopping behavior as well as on the perceived contribution of a shopping channel to their well-being, with a focus on individuals who perceive themselves as being socially excluded, particularly by mobility disability. The project was carried out in the United States using an online survey (n = 1,220). Social exclusion has a positive statistically significant effect on respondents’ self-connection with all channels; for many socially excluded respondents the shopping channel has an important role in their lives. Self-connection with the channel has a positive effect on value co-creation and there is a positive relationship between value co-creation and the perceived contribution of the channel on well-being. When consumers help other individuals in their decision making they not only create value for the retailer and for other customers but also contribute positively to their own well-being. Importantly, for smart shopping channels where consumers use a computer or a mobile phone, the effects of value co-creation on the perceived contribution of these channels to consumer well-being are stronger for shoppers with a mobility disability than for those without such a disability.
Keywords: Mobility disability; Multichannel shopping; Shopping channels; Smart shopping channels; Social exclusion; Value co-creation; Well-being